Physical activity and health-related quality of life in older adults: depression as a mediator - Xiuxiu Li; Pengfei Wang; Yihua Jiang; Yinghua Yang; Feng Wang; Fei Yan; Ming Li; Wenjia Peng; Ying Wang (BMC Geriatrics, 2024)
Abstract Background Physical activity(PA) is associated with health-related quality of life (HRQoL) among older adults, and both are associated with mood, such as depression. However, the indirect effects of PA on HRQoL in older adults have not been clearly established. This study explained how different types and intensities of PA were associated with HRQoL while considering the effects of depression in older adults. Methods A cross-sectional study was conducted with 7,518 community-dwelling older adults aged 60 years and older. PA (leisure-time, household, and work-related), depression, and HRQoL were measured using the Physical Activity Scale for the Elderly (PASE), the 30-item Geriatric Depression Scale (GDS-30), and the 36-Item Short-Form Health Survey (SF-36), respectively. Information on age, gender, education, monthly income, activities of daily living, smoking, and alcohol drinking was also collected. Regression analysis was used to explore the relationship between PA, depression and HRQoL, and a mediation effect test process was used to verify the mediating mechanism of the depression on this relationship. Results The study showed that after adjusting for a set of covariates, SF-36 Physical Component Summary (PCS) scores were negatively associated with depression (B = -2.046, 95% CI [2.584, -1.509]) and positively with PA (p < 0.001). Similarly, SF-36 Mental Component Summary (MCS) scores were negatively associated with depression (B = -11.657, 95% CI [-12.190, -11.124]). In mediation analyses, we found that depression partially mediated the relationship between different types and intensities PA and PCS (moderate leisure-time PA: B = 0.223, 95%CI [0.153,0.293], P < 0.001; vigorous leisure-time PA: B = 0.323, 95%CI [0.232,0.413], P < 0.001; moderate household PA: B = 0.092, 95%CI [0.045,0.139], P < 0.001; vigorous household PA: B = 0.137, 95%CI [0.085,0.190], P < 0.001; work-related PA: B = 0.193, 95%CI [0.658,0.190], P < 0.001) and MCS (moderate leisure-time PA: B = 1.243, 95%CI [1.008,1.479], P < 0.001; vigorous leisure-time PA: B = 1.800, 95%CI [1.585,2.015], P < 0.001; moderate household PA: B = 0.496, 95%CI [0.274,0.718], P < 0.001; vigorous household PA: B = 0.742, 95%CI [0.521,0.963], P < 0.001; work-related PA: B = 1.026, 95%CI [0.819,1.234], P < 0.001). Conclusions This study suggested that leisure-time, household, and work-related PA were negatively associated with depression, while positively affecting HRQoL in Chinese older adults. The relationships between different types and intensities of PA and HRQoL were mediated by depression. Interventions aimed at promoting purposeful exercise and different types of PA may have mental health benefits. It is recommended that geriatric health managers and healthcare planners prioritize interventions to help improve PA intensities, alleviate depressive symptoms to promote beneficial effects on HRQoL in older adults.